S(Ns)= Ns - N taking the denominator of the RHS to LHS

S(Ns) - Ns = -N (taking Ns to the LHS from RHS)

Ns - S(Ns) = N (rearranging the terms to make N on the RHS positive)

Ns (1 - S) = N (rearranging the LHS)

Therefore,

Ns = N / (1-S).

George,Y

2006-03-24 02:14:34

(Ns - N) / (Ns)=Ns/Ns-N/(Ns)=1-1/s

As long as S=1-1/s, no matter what N is ,the equation S = (Ns - N) / (Ns) is valid. That means N is Undetermined by this equation! (N can be any number)

another example a+2N=a+N+N, can you solve N out?

DodgyPerson

2006-03-24 02:03:46

Ok i know it might be very simple for some people out here, but i am struggling with it:

I need to re-arrange the following formula in way so i can get Ns on its own!!!!

S = (Ns - N) / (Ns)

So as i said, i cant get Ns on its own!!!! WOuld be greatful if anyone could help!!!!